Employment contract in Malaysia - Ismail, Fadillah; Chan, Shiau Wei; Maulad Bahrol, Khadijah; Abdullah, Mohd Fahmy (Penerbit Uthm, 2019)
According to Murray (2018), employees is a person who performs services under an organisation and their respective organisation can control the action of that person in that specific organisation. An organisation, institution, government entity, agency, company, professional services firm or small business who controls and directs an employees under an implied contract and pay them salary know as an employer (M. Heathfield, 2018). An agreement occurs between an employee and employer known as employment contract. An employment contract is a written document where states the rights and responsibilities of the two parties (Doyle, 2018).